Back Cover: Di‐ and Trinuclear Gold Complexes of Diphenylphosphinoethyl‐Functionalised Imidazolium Salts and their N‐Heterocyclic Carbenes: Synthesis and Photophysical Properties (Chem. Eur. J. 2/2015). Issue 2 (7th January 2015) - Bestgen, Sebastian; Gamer, Michael T.; Lebedkin, Sergei; Kappes, Manfred M.; Roesky, Peter W.
<x xml:space="preserve">Abstract</x> A novel and neutral trinuclear gold complex ligated by a phosphinoethyl functionalised NHC is highlighted in the middle of the picture. The complex is carried and lifted by three laborious golden bears. Furthermore, the molecule is surrounded by the terms "aurophilicity" and "photoluminescence": both of these very interesting characteristics were unified and studied in the compounds reported in the Full Paper by P. W. Roesky et al. on page 601 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>